Intergenerational Care and Subjective Well-being: A Study of the Particularities of Ageing Amongst the Indigenous Peoples of Chile. - Valencia-Gálvez, Lorena; Gallardo-Peralta, Lorena; Andrade-Guzmán, Carlos; Rain-Rain, Alicia; Rodriguez-Venegas, Viviana (British Journal of Social Work, 2025)
This empirical study explores intergenerational caregiving and subjective well-being amongst older adults in Indigenous communities in rural Chile. Facing substantial social and economic challenges, these communities depend heavily on cultural traditions and family support systems. Data were collected from 1,348 older adults, aged sixty and above, using surveys to assess caregiving practices, intergenerational support and subjective well-being, measured by the Personal Wellbeing Index and the Perceived Social Support Questionnaire. Findings reveal that caregiving is deeply rooted in cultural and historical contexts, with positive aspects such as increased satisfaction and social connectedness, and negative aspects including stress and social isolation. Women predominantly assume caregiving roles, maintaining cultural traditions and supporting family well-being. Notable differences in intergenerational support and subjective well-being were observed based on ethnic group and gender. The implications for social work practice are insightful. The study highlights the need for culturally sensitive social work policies and inclusive strategies that address the well-being of older adults in these communities. Social workers and policymakers must consider cultural nuances and the unique needs of Indigenous populations, taking into account cultural identity, economic conditions and acculturation to develop effective support programmes.